2017
DOI: 10.1152/ajpgi.00180.2017
|View full text |Cite
|
Sign up to set email alerts
|

Vagally mediated effects of brain stem dopamine on gastric tone and phasic contractions of the rat

Abstract: Dopamine (DA)-containing fibers and neurons are embedded within the brain stem dorsal vagal complex (DVC); we have shown previously that DA modulates the membrane properties of neurons of the dorsal motor nucleus of the vagus (DMV) via DA1 and DA2 receptors. The vagally dependent modulation of gastric tone and phasic contractions, i.e., motility, by DA, however, has not been characterized. With the use of microinjections of DA in the DVC while recording gastric tone and motility, the aims of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
4
20
0
Order By: Relevance
“…These data support further the monosynaptic nature and tonic excitatory influence on DMV neurons, vagal efferent outflow, and gastric motor functions of this pathway. Interestingly, while microinjection of dopamine in the DVC is gastroinhibitory via DA2-mediated actions 22 , here we show that the response to benztropine is mediated via DA1 receptors. These data suggest strongly that the nigro-vagal fibers target selective subpopulations of DMV neurons dedicated to modulation of specific neurocircuits; the observation is supported also by the differential responses on tone vs motility obtained with yohimbine pretreatment.…”
Section: Discussionmentioning
confidence: 50%
“…These data support further the monosynaptic nature and tonic excitatory influence on DMV neurons, vagal efferent outflow, and gastric motor functions of this pathway. Interestingly, while microinjection of dopamine in the DVC is gastroinhibitory via DA2-mediated actions 22 , here we show that the response to benztropine is mediated via DA1 receptors. These data suggest strongly that the nigro-vagal fibers target selective subpopulations of DMV neurons dedicated to modulation of specific neurocircuits; the observation is supported also by the differential responses on tone vs motility obtained with yohimbine pretreatment.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, DA2 receptor‐mediated effect is more prominent than the DA1 receptor‐mediated effects . Thus, stimulation of dopaminergic projections of substantia nigra pars compacta (SNpc) causes some gastric excitation due to stimulation of DA1 receptors on the DMV‐C‐e neurons .…”
Section: Gastric Excitatory Vagal Motor Circuit (Gevmc)mentioning
confidence: 99%
“…exert different effects on vagal circuits, based on the receptor type and the neural input. For example, dopamine may use either stimulatory effect via the dopamine 1 (DA1) receptors or inhibitory effect via the dopamine 2 (DA2) receptors on the DMV neurons of the GEVC.Moreover, DA2 receptor-mediated effect is more prominent than the DA1 receptor-mediated effects 77. Thus, stimulation of dopaminergic projections of substantia nigra pars compacta (SNpc) causes some gastric excitation due to stimulation of DA1 receptors on the DMV-C-e neurons 77.…”
mentioning
confidence: 99%
“…Previous work has shown that elevated levels of brain stem dopamine lead to reduced food intake [21] and gastric relaxation [22]. Moreover, dopamine administration in the brain stem reduced gastric tone and motility which was abolished by vagotomy [18]. Studies linking alterations in vagal signaling to the development of Parkinson's disease [23,24] further support the assumption of afferent signaling between the gut and key dopaminergic brain regions along the vagal pathway.…”
Section: Discussionmentioning
confidence: 84%
“…Afferently, stimulation of the vagal sensory ganglion in mice was found to induce dopamine release in the substantia nigra [17]. Efferently, dopamine administration to the dorsal vagal complex in rats modulated the upper gastrointestinal tract by reducing gastric tone and motility via DA2 receptors in the dorsal motor nucleus of the vagus [18]. Thus, while vagal stimulation mostly targets afferent pathways, studies in rodents provide evidence for brain-mediated effects on downstream targets.…”
Section: Introductionmentioning
confidence: 99%